The Influence of Digestive Tract Length of Larvivorous Fish Related to Predation Potential on Aedes aegypti Larvae - Satoto, Tri Baskoro Tunggul; Sukendra, Dyah Mahendrasari; Hardaningsih, Ignatius; Diptyanusa, Ajib (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
Biological vector control by using larvivorous fish will be beneficial in reducing Aedes aegypti population, hence reducing risk of dengue virus transmission. It is important to select the larvivorous fish according to its digestive organ.Current study aimed to investigate the predation potential among the fish species and to identify the influence of the digestive tract length of the fish related to their predation potential. The research was an analytical observational study with post-test only design. Third stage larvae of Aedes aegypti were used as preys for tilapia (Oreochromis niloticus), common carper (Cyprinus carpio), and guppy (Poecillia reticulata). In association with their digestive tract length, predation potential of tilapia, common carper, and guppy showed statistical differences (P<0.05). Tilapia demonstrated highest predation of the larvae, followed by common carper and guppy. There are associations between difference in shapes of mouth and intestines, mouth width, intestinal length, and predation potential of these fish species. Current study results showed possible associations between digestive tract length of tilapia, common carper and guppy and predation potential on Aedes aegypti larvae, allowing these fish species to be used inbiological control of Aedes aegypti.